Fabrication of Fibrous Materials Based on Cyclodextrin and Egg Shell Waste as an Affordable Composite for Dental Applications - Amini, Amirhesam; Kazemzadeh, Parya; Jafari, Mojtaba; Moghaddam-Manesh, Mohammadreza; Chauhan, Narendra Pal Singh; Fazelian, Nafiseh; Sargazi, Ghasem (Frontiers in Materials, 2022)
In this study, the fibrous nanostructures based on cyclodextrin from egg shell waste were fabricated using electrospinning technique under optimal conditions. Scanning electron microscopy (SEM), thermal stability analysis and abrasion testing were used to characterise the final products. The cyclodextrin nanofibrous products were used as new nanostructures in the field of dental coatings due to the obtained properties such as uniform shape, small particle size distribution, high thermal stability and optimal abrasion resistance. The DFT calculations confirmed the chemical stability of the final products. The MTT test results confirmed that the fibrous nanocoatings of the egg shell have no significant side effects on healthy cells. These fibrous nanostructures could be a promising candidate for use as a dental nanocoating material.